THE PLIGHT OF ALMAJIRAI AND CHILDREN OF NOMADIC HERDSMEN AS CONTRIBUTORS TO EDUCATIONAL INEQUALITY IN NIGERIA - Eyitayo Olufunmilayo, Akinyemi (Journal of Continuing and Development Education, 2023)
This paper identified the situation of Almajirai and children of nomadic herdsmen; factors inhibiting Almajirai and herdsmen children from accessing western education; efforts of the society at making Almajirai and nomadic herdsmen children attain western education; implications of their refusal to access western education on the society; how the Almajirai and children of nomadic herdsmen have contributed to inequality of education in Nigeria; and the framework for effective formal system of education for Almajirai and the children of nomadic herdsmen. This paper concluded that culture, and ignorance of the importance of western education has been the major factors preventing the Almajirai and nomadic Fulani herdsmen’ children from going to school. The paper among other things recommended that parents of the Almajirai and nomadic Fulani herdsmen give proper care and stop denying children their rights to western education; social workers visit, counsel and provide necessary amenities that could motivate the Almajirai, and the children of nomadic herdsmen embrace western education to ensure equality in educational system in Nigeria.